Primary hypoparathyroidism presenting as refractory status epilepticus (Bangladesh Critical Care Journal, 2013)
A case of adult onset primary hypoparathyroidism is reported highlighting the effect of phenytoin therapy on calcium metabolism. This patient of brain calcinosis syndrome (BCS) presented with refractory status epilepticus despite on full dose phenytoin. Seizures were controlled with correction of hypocalcemia. A change of anti-epileptic therapy to lamotrigine and supplementation with calcium and calcitriol kept the patient seizure free for last 10 months till last follow up. DOI: http://dx.doi.org/10.3329/bccj.v1i2.17203 Bangladesh Crit Care J September 2013; 1 (2): 99-101